2019
DOI: 10.3390/ijerph16183286
|View full text |Cite
|
Sign up to set email alerts
|

Acute Health Impacts of the Southeast Asian Transboundary Haze Problem—A Review

Abstract: Air pollution has emerged as one of the world’s largest environmental health threats, with various studies demonstrating associations between exposure to air pollution and respiratory and cardiovascular diseases. Regional air quality in Southeast Asia has been seasonally affected by the transboundary haze problem, which has often been the result of forest fires from “slash-and-burn” farming methods. In light of growing public health concerns, recent studies have begun to examine the health effects of this seas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
75
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 39 publications
1
75
0
1
Order By: Relevance
“…The results of a study by Kunzli et al [15] showed that, in European countries like Austria, France, and Switzerland, air pollution is the cause of death of more than 40,000 people. As well, previous studies in Southeast Asia demonstrated a significant association between an increase in mortality and Pollutants Standards Index [16][17][18][19][20]. Likewise, trends in low birth weight, neonatal deaths, fetal and infant mortality, spontaneous abortion, and the occurrence of birth defects were found to correspond closely with quantities of outdoor pollution [21][22][23][24][25].…”
Section: Introductionsupporting
confidence: 74%
“…The results of a study by Kunzli et al [15] showed that, in European countries like Austria, France, and Switzerland, air pollution is the cause of death of more than 40,000 people. As well, previous studies in Southeast Asia demonstrated a significant association between an increase in mortality and Pollutants Standards Index [16][17][18][19][20]. Likewise, trends in low birth weight, neonatal deaths, fetal and infant mortality, spontaneous abortion, and the occurrence of birth defects were found to correspond closely with quantities of outdoor pollution [21][22][23][24][25].…”
Section: Introductionsupporting
confidence: 74%
“…In this study, we have demonstrated an association between exposure to elevated PSI levels and an increased short-term risk of mortality in Singapore. Air pollution is a tremendous public health issue, and our study has incorporated the Singapore context into the existing and growing body of evidence on the effect of air pollution on health [12,22,[52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Haze occurs annually due to periodic biomass burning, such as forest fires, peatland combustion, and agricultural burning in Sumatra and Kalimantan, Indonesia. The influence of unpredictable monsoon rain and El-Nino phenomenon both worsens the transboundary haze due to the prolonged and drier weather conditions, especially during the southwest monsoon season [3][4][5][6][7][8]. These conditions increase the severity of air quality due to it containing a noxious mix of air pollutants, such as particulate matter and noxious gases, which are collectively influenced by meteorological factors like ambient temperature, relative humidity, and wind speed [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The small particulate size contained in haze can easily penetrate the lung; at worst, it also goes into the bloodstream [22]. Based on the previous study by [4], long-term exposure to air pollution causes an increase in neurological diseases such as cerebrovascular disease and stroke, along with headache and migraine symptoms. Skin is one of the organs that are directly in contact with air pollution, especially during transboundary haze events.…”
Section: Introductionmentioning
confidence: 99%